2012
DOI: 10.3896/ibra.1.51.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Composition and antioxidant activity of honey from Africanized and stingless bees in Alagoas (Brazil): a multivariate analysis

Abstract: 2012) Composition and antioxidant activity of honey from Africanized and stingless bees in Alagoas (Brazil): a multivariate analysis, Journal of Apicultural Research, 51:1, 23-35 To link to this article: http://dx. SummaryThe purpose of this study was to evaluate the antioxidant activity of honey from different entomological sources which were harvested in the dry season of 2008-2009 from distinct mesoregions of the State of Alagoas in the North East of Brazil. Honey produced by five different species of bees,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 19 publications
3
29
1
1
Order By: Relevance
“…Aforesaid reviews indicated that free radicals and nitric oxide signaling play critical roles in the growth of opioid analgesic tolerance and dependence, and radical scavenging agents, as well as nitric oxide synthase inhibitors, can be possibly implemented within the avoidance of morphine tolerance and withdrawal syndrome 5,21,22,2,4 . The excessive antioxidant activity of honey and its compounds have been discovered in common reports 23,24,26,27,28 . Moreover, a bioactive component of honey along with a phenolic compound, adequately overthrows gathering of reactive oxygen and nitrogen species and re-establishes endogenous antioxidant glutathione degrees and up-regulates the countenance of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Aforesaid reviews indicated that free radicals and nitric oxide signaling play critical roles in the growth of opioid analgesic tolerance and dependence, and radical scavenging agents, as well as nitric oxide synthase inhibitors, can be possibly implemented within the avoidance of morphine tolerance and withdrawal syndrome 5,21,22,2,4 . The excessive antioxidant activity of honey and its compounds have been discovered in common reports 23,24,26,27,28 . Moreover, a bioactive component of honey along with a phenolic compound, adequately overthrows gathering of reactive oxygen and nitrogen species and re-establishes endogenous antioxidant glutathione degrees and up-regulates the countenance of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…which is 106.01 ± 9.85 mg GA equivalent/ 100g compared to Apis sp. 92.34 ± 13.55 mg GA acid equivalent/ 100 g (Duarte et al, 2012). Meanwhile for antioxidant activity of Plebeia spp.…”
Section: Antioxidant Properties Of Stingless Bee Honeymentioning
confidence: 99%
“…Previous study showed that stingless bee honey can act as anti-inflammatory (Borsato et al, 2014), anticancer (Kustiawan et al, 2014;Yazan et al, 2016), antimicrobial (Miorin et al, 2003;Demera et al, 2004;Garedew et al, 2004;Temaru et al, 2007;Kimoto-Nira and Amano, 2008;Chanchao et al, 2009;Boorn et al, 2010;Rodríguez et al, 2012;Ilechie et al, 2012;Andualem, 2013;Ewnetu et al, 2013;Mercês et al, 2013;Queiroz et al, 2013;Zainol et al, 2013;Nobre da Cruz et al, 2014;Massaro et al, 2014;Zamora et al, 2014;Medeiros et al, 2016;De Sousa et al, 2016; and possessed antioxidant properties (Duarte et al, 2012;Almeida da Silva et al, 2013;De Sousa et al, 2016). However, the beneficial of stingless bee honey has been abandoned in modern medicine due to the paucity of systematic scientific studies for supporting its medical properties (Pe´rez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 60 days, every 72 hours for more 16 days, the rats were force-feeding with 1mL of the specific therapy, using an inox gavage cannula. The quality safety and composition of the honey used in this work was previously analyzed, as soon as it was harvested, in September/2009 (Duarte, 2009;Duarte et al, 2012). Dnce all the treatments had been carried out, the animals underwent anesthesia and surgical removal of their stomach, which were excised, fixed, included in paraffin, sectioned, stained and macro and microscopically analyzed as previously described.…”
Section: Evaluation Of Anti-ulcer Activitymentioning
confidence: 99%